The Selection of Storage Period for Fresh Rice Noodles, Processing Materials, and the Screening of Key Indicators - Zhe Yang; Peng Liu; Xilin Fang; Guanghui Chen (Foods, 2024)
The storage period of paddy is a critical factor affecting rice quality, and it is still unclear how fresh rice noodles, primarily made from paddy, respond to changes in the storage period. To elucidate the relationship between the paddy storage period and the quality of fresh rice noodles, this study used fourteen rice varieties as materials and set up three paddy storage periods (six months, nine months, and twelve months). It explored the quality variation patterns of fresh rice noodles processed from these paddies and analyzed the relationship between the two in conjunction with rice quality. The results indicated that fresh rice noodles produced from paddies stored for nine months exhibited superior quality compared to the other two storage periods. Grey relational analysis and correlation analysis confirmed that this was primarily attributed to changes in the gel consistency of the paddy. When the paddy was stored for nine months and the rice gel consistency was approximately 32 mm, the quality of the fresh rice noodles produced was optimal, serving as an important basis for selecting raw materials for fresh rice noodles.